Use of internet social networks in academic environment - Cenková, Renáta (Array, 2020)
Numerous national and private Slovak universities and colleges are currently confronted with a state, where the offer of study programmes exceeds its demand - students’ interests. This paper describes reasons for this situation but mainly it points out the fact that the advent of information and communication technologies significantly intervened in different areas of life and all types of communication. The implementation of some tools of internet social networks in the academic environment is, therefore, essential. In addition to the theoretical background, the paper also includes case study related to the creation of a new Facebook profile #MaŠtu, setting up specific online marketing key performance indicators (KPI) and monitoring them using both Facebook analytics metrics and the social networking tool for administration, ZoomSphere.